1017 Early Mobilisation After Stable Distal Radius Fracture – an Audit of BOAST Guideline Adherence. (19th August 2022) - Stewart, RJ; Abdelghafour, K; Abdelhakim-Edres, K; Sokota, S; Narang, K; Ray, A
Abstract: Aim: Distal radius (DR) fractures are among the commonest fractures seen by orthopaedics. The management of these fractures is dependent on the stability of the fracture, and conservative management is usually favoured for stable fractures. Mobilisation of the wrist following this stable fracture is necessary to avoid the risks of wrist stiffness, complex regional pain syndrome and limitation of function. According to BOAST guidelines for management of DR fractures: patients with a stable fracture should be considered for early mobilisation with a removable support once pain allows. The aim of this study was to determine our unit's adherence to guidelines and review the period of immobilisation of stable DR fractures. Method: Retrospective analysis of virtual fracture clinic referrals, ED and clinic notes, imaging and any further correspondence of patients referred to our orthopaedic team between 1/2/20–30/7/20 with isolated DR fracture. Results: Of 163 patients referred with DR fracture, 49.7% were deemed to have a stable fracture. Of these patients, only 37% were mobilised early, with the remainder fully immobilised for 6 weeks without active mobilisation protocol. Conclusions: A large proportion of patients with stable fractures are not being managed in accordance with BOAST guidelines, therefore a standardised intervention is needed to ensure patients regain maximum possible function. We propose that a new protocol is put in place to screen all DR fractures within our virtual fracture clinic into stable v. unstable pattern and if deemed stable to ensure patient is seen for early physiotherapy face to face or virtually.